Water footprint in family farming (Research, Society and Development, 2021)
Currently, the management of water resources has gained greater visibility and has become indispensable, with the need for different methodologies which consider all water used and incorporated in the processes and products. In this way, the water footprint concept has been introduced to calculate the appropriation of fresh water on the part of the humankind. Thus, the objective of this work was to determine the water footprint in some sectors of family farming in the municipality of Teófilo Otoni – MG, analyzing the agricultural production of crops cultivated exclusively by the sector in 2017 in Teófilo Otoni. The cultivation of pumpkin, banana, chayote, beans, cassava, Maize, peppers, okra, cabbage, and tangerine were studied. Thus, the total water footprint for the year 2017 was 13,996,735.05 m3.t-1, in which the green water footprint represents 86%, the blue water footprint represents 12.5% and the gray water footprint equals 1.5%. The family farming sector of Teófilo Otoni demands an average of 196.73 liters for a production of R$ 1.00.